The degree of food processing can influence serum fatty acid and lipid profiles in women with severe obesity - Lopes, Karem Lays Soares; Figueiredo, Nayra; Kattah, Fabiana Martins; Lima, Glaucia Carielo; Oliveira, Emilly Santos; Horst, Maria Aderuza; Oyama, Lila Missae; Dâmaso, Ana Raimunda; Whitton, Renata Guimarães Moreira; de Souza Abreu, Valéria; Duarte, Amélia Cristina Stival; Pimentel, Gustavo Duarte; et al. (Frontiers in Nutrition, 2023)
Background: The increase in the prevalence of obesity is associated with the increase in the consumption of ultra-processed foods and may be related to the increase in the disorders involving metabolism and the transport and storage of fatty acids. Objective: To evaluate the effect of processed food consumption according to the degree of processing on the serum fatty acid levels and lipid profile of women with severe obesity. Methods: This was a cross-sectional study. Data were collected from anthropometric assessments, the food frequency questionnaire (FFQ), and blood tests for lipidogram studies and serum fatty acid measurements. The foods consumed were identified through the FFQ and classified according to the degree of processing based on the NOVA rating, and the frequencies of consumption were transformed into scores, as proposed by Fornés methodology. Data were analyzed using IBM SPSS Statistics, version 21. The significance level for the analysis was set at 5%. Results: This study included 44 women with a mean age of 40.59 years and mean body mass index of 48.61 kg/m2. An inverse association was observed between the consumption of unprocessed and the occurrence of hypertriglyceridemia (p = 0.021) and levels of triglycerides (p = 0.047), total cholesterol (p = 0.030), and very low-density lipoprotein-cholesterol (p = 0.039). The consumption of processed foods was positively associated with the presence of hypertriglyceridemia (p = 0.044) and omega 6/3 ratio (p = 0.001) and negatively associated with total omega 3 levels (p = 0.011). The consumption of processed foods was positively associated with total cholesterol (p = 0.041) and negatively associated with the omega 3/6 ratio (p = 0.001). A negative correlation was found between the average consumption of ultra-processed foods (at least once a week) and serum level of high-density lipoprotein (p = 0.035). Conclusion: The consumption of processed and ultra-processed foods was associated with unfavorable lipid profiles and fatty acid levels in women with severe obesity. These results emphasize the importance of promoting the consumption of unprocessed food to mitigate metabolic disorders linked to processed food intake.